Pengaruh Kualitas Produk dan Brand Equity terhadap Keputusan Pembelian Konsumen dengan Meningkatkan Penjualan sebagai Variabel Intervening pada Produk Skincare Scarlet Whitening (Studi Kasus pada Mahasiswa Universitas Putra Indonesia “YPTK” Padang) - Rahul Fadrian; Vicky Brama Kumbara; Agam Mei Yudha (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to test how much influence Product Quality and Brand Equity have on Consumer Purchasing Decisions by Increasing Sales as an Intervening Variable on Scarlet Whitening Skincare Products (Case Study on Students of Putra Indonesia University "YPTK" Padang). The sample in this study amounted to 108 respondents in scarlet whitening skincare customers. This population is 2021 management students of Putra Indonesia University YPTK Padang.The results of this study are (1) There is a positive and significant influence between Product Quality on Sales Increase in Scarlet Whitening Skincare Products. (2) There is a positive and significant influence between Brand Equity on Sales Increase in Scarlet Whitening Skincare Products. (3) There is a positive and significant influence between Product Quality on Purchasing Decisions on Scarlet Whitening Skincare Products. (4) There is a negative and insignificant influence between Brand Equity on Purchasing Decisions on Scarlet Whitening Skincare Products. (5) There is a positive and significant influence between Sales Increase on Purchasing Decisions on Scarlet Whitening Skincare Products. (6) Sales Increase mediates Product Quality on Purchasing Decisions on Scarlet Whitening Skincare Products (7) Sales Increase mediates Brand Equity on Purchasing Decisions on Scarlet Whitening Skincare Products.